ARMSprimer3: An open-source primer design Python program for amplification refractory mutation system PCR (ARMS-PCR) - Jingwen Guo; Jeremy Grojean; Huazhang Guo (Journal of Pathology Informatics)
Single nucleotide polymorphisms (SNPs) are DNA sequence variations of a single base pair. They are the underlying mechanism of most human genetic variation and etiology of many heritable human diseases. SNPs can be reliably detected by amplification refractory mutation system PCR (ARMS-PCR). ARMS-PCR is based on allele-specific PCR primers that only amplify DNA samples with the target allele and do not amplify DNA samples without the target allele. In addition to the allele-specific mismatch at the 3′ end, ARMS-PCR introduces additional deliberate mismatches near the 3′ end of the allele-specific primers to further destabilize the non-specific binding and priming on non-target alleles. This modification increases the specificity for SNP detection, but also increases the complexity of PCR primer design. We developed ARMSprimer3, a Python program to automate the ARMS-PCR primer design process. The validity of ARMSprimer3 was confirmed by successfully using it to develop diagnostic tests in our clinical molecular diagnostic lab. ARMSprimer3 is open-source software and can be freely downloaded from https://github.com/PCRPrimerDesign/ARMSprimer3.